2019
DOI: 10.18295/squmj.2018.18.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Cross-Cultural Heart Failure-Specific Quality of Life Questionnaire

Abstract: Objectives: Heart failure (HF) is a common clinical syndrome with an enormous impact on prognosis and lifestyle. Accordingly, rehabilitation measures need to be patient-specific and consider various sociocultural factors so as to improve the patient’s quality of life (QOL). This study aimed to develop and validate a HF-specific QOL (HFQOL) questionnaire within a multicultural setting. Methods: This study took place at the National Heart Institute and Universiti Kebangsaan Malaysia Medical Centre, Kuala Lumpur,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…A probable mechanism explaining the above-mentioned effects would be disturbances in the cellular architecture of diabetics, evoked by severe pro-oxidative stress. 38,39 The production of oxidants can induce apoptosis in hepatocytes and can induce oxidative stress, which is an indicator of these disturbances. 38 Notably, it is found that hyperglycemia decreases the synthesis and activity of some antioxidizing enzymes, such as SOD and GPx, likely via a glycation process.…”
Section: Studying the Protective Role Of Vple In The Livers Of Streptmentioning
confidence: 99%
See 3 more Smart Citations
“…A probable mechanism explaining the above-mentioned effects would be disturbances in the cellular architecture of diabetics, evoked by severe pro-oxidative stress. 38,39 The production of oxidants can induce apoptosis in hepatocytes and can induce oxidative stress, which is an indicator of these disturbances. 38 Notably, it is found that hyperglycemia decreases the synthesis and activity of some antioxidizing enzymes, such as SOD and GPx, likely via a glycation process.…”
Section: Studying the Protective Role Of Vple In The Livers Of Streptmentioning
confidence: 99%
“…The inhibitory effects of VPLE could be related to the antioxidant activity of VPLE. 38,53,54 The remarkable free radical scavenging activity of VPLE could be a potential reason for its effects on reversing lipid peroxidation levels and on the antioxidant activities of SOD and GPx enzymes.…”
Section: Studying the Protective Role Of Vple In The Livers Of Streptmentioning
confidence: 99%
See 2 more Smart Citations
“…It is when the heart muscle is not able to efficiently pump sufficient blood and oxygen in order to meet the needs of the body. In accordance to that, rehabilitation measures need be tailored to the patients considering various sociocultural factors as a result to improve the quality of life (QOL) among the patients (Mohamed, Ghazali, Yaacob, Azan & Maskon, 2018). Past research have suggested that HF patients have suffered from a bad quality of life (Napier, McNulty, Eton, Redfield, AbouEzzeddine & Dunlay, 2018).…”
Section: Introductionmentioning
confidence: 99%